Cutting-edge techniques provide insights regarding repeated implantation failure patients. Issue 4 (April 2023) - Govahi, Azam; Nasr-Esfahani, Mohammad-Hossein; Amjadi, Fatemehsadat; Mahdevar, Mohammad; Mehdizadeh, Rana; Mehdizadeh, Mehdi
Abstract: Research question: Can time-lapse parameters and the transcriptional profile of cumulus cells be used to achieve a more stringent and non-invasive method of embryo assessment and to identify possible factors affecting the embryo's ability to implant in repeated implantation failure (RIF) patients? Design: A total of 190 embryos from 18 oocyte donors and 145 embryos from 15 RIF patients were evaluated based on time-lapse parameters. Three morphokinetic parameters including T5 (time to reach five cells), T3 (time to reach three cells) and CC2 (time to two to three cells) were recorded for all embryos. Embryos that had all three parameters in the normal range were graded as high quality and comparison between these parameters were compared in high-quality embryos between two groups. The transcriptional profile of cumulus cells related to high-quality embryos of both groups were analysed by RNA sequencing and compared. Finally, the possible relationship between differentially expressed genes and time-lapse parameters was examined. Results: T5 was significantly lower in the RIF group than the donor group ( P  = 0.011). The cumulus cell transcriptome analysis showed 193 genes were down-regulated and 222 genes up-regulated. The mammalian target of rapamycin and the transforming growth factor beta pathways were significantly increased in the RIF group compared to the donor group ( P  = 0.007 and 0.01, respectively). Vitamin B12 and fatty acid beta-oxidation pathways were also significantly reduced in the RIF group compared to the donor group ( P  = 0.006 and 0.01, respectively). Conclusions: Differences in the transcriptomic profiles of cumulus cells and some morphokinetic parameters may be one of the main factors contributing to unexplained RIF. Graphical Abstract: Image, graphical abstract